PENGEMBANGAN MEDIA JOB SHEET UNTUK SUMBER BELAJAR PRAKTEK SISTEM REM SISWA KELAS XI TEKNIK KENDARAAN RINGAN OTOMOTIF DI SMK MA’ARIF NU 1 AJIBARANG - Habib Ramdhan Prakoso; subagyo (Universitas Sarjanawiyata Tamansiswa Yogyakarta, 2025)
The goal of this study was to ascertain the relationship between class XI students at SMK Tamansiswa Jetis Yogyakarta's learning achievement of creative goods and entrepreneurship as well as learning motivation partially and concurrently with their interest in entrepreneurship. Ex-post facto research is the type used in this study. Using a questionnaire to gauge students' desire for learning, interest in entrepreneurship, and knowledge of creative products and entrepreneurship topics are some methods of data collecting. A questionnaire is the research's primary tool. Multiple regression analysis was employed in the data analysis technique to test the first hypothesis, and partial correlation tests were performed to test the second and third hypotheses. The findings revealed that (1) there was an association between the creation of creative products and entrepreneurship, as well as between learning motivation and interest in entrepreneurship, with a value of F = 43,047 and a significance value of 0.000 0.05. (2) The achievement of innovative and entrepreneurial products and interest in entrepreneurship are positively and significantly correlated, with a correlation coefficient value of r count = 0.372 > rtable = 0.276 and a significant level of 0.008 0.05. (3) With a coefficient of r count = 0.706 > rtable = 0.276 and a significance level of 0.000 0.05, there is a substantial and positive association between learning motivation and interest in entrepreneurship.